Green communications : principles, concepts and practice - Samdanis, Konstantinos (Chichester, West Sussex, United Kingdom : Wiley, 2015)
Written in a tutorial style that contains well-established solutions, this book aims to elaborate the fundamentals of energy efficiency and green communications, exploring the main challenges, mechanisms and practice considering both wireless and wireline systems. --
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Telecommunication -- Energy conservation; Green technology; Engineering economy; Sustainable engineering; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Electronic books; Electronic books